Income-, education- and gender-related inequalities in out-of-pocket health-care payments for 65+ patients - a systematic review - Corrieri Sandro; Heider Dirk; Matschinger Herbert; Lehnert Thomas; Raum Elke; König Hans-Helmut (International Journal for Equity in Health, 2010)
Abstract Background In all OECD countries, there is a trend to increasing patients' copayments in order to balance rising overall health-care costs. This systematic review focuses on inequalities concerning the amount of out-of-pocket payments (OOPP) associated with income, education or gender in the Elderly aged 65+. Methods Based on an online search (PubMed), 29 studies providing information on OOPP of 65+ beneficiaries in relation to income, education and gender were reviewed. Results Low-income individuals pay the highest OOPP in relation to their earnings. Prescription drugs account for the biggest share. A lower educational level is associated with higher OOPP for prescription drugs and a higher probability of insufficient insurance protection. Generally, women face higher OOPP due to their lower income and lower labour participation rate, as well as less employer-sponsored health-care. Conclusions While most studies found educational and gender inequalities to be associated with income, there might also be effects induced solely by education; for example, an unhealthy lifestyle leading to higher payments for lower-educated people, or exclusively gender-induced effects, like sex-specific illnesses. Based on the considered studies, an explanation for inequalities in OOPP by these factors remains ambiguous.